China’s Agricultural Greenhouse Gas Emissions and Reduction Strategies - Shenghui HAN; Wen ZHANG; Dongjie CHEN; Yongqiang YU; Xunhua ZHENG; Wei ZHANG; Siqi LI (Chinese Journal of Urban and Environmental Studies)
Based on the data of China’s agricultural greenhouse gas (GHG) emissions from previous national GHG inventories, the Food and Agriculture Organization (FAO) of the United Nations database and related literature, this paper systematically analyzes recent trends in China’s total agricultural GHG sources, sinks and emissions intensity from multiple perspectives. The results show that from 2005 to 2021, China’s annual agricultural GHG emissions increased from 859 million to 931 million tons of carbon dioxide equivalent (MtCO2e), while the net carbon sequestration in agricultural soils grew from 41 MtCO2e to 106 MtCO2e. Specifically, agricultural methane (CH4) emissions accounted for 68%–73% of the total agricultural emissions, higher than agricultural nitrous oxide (N2O) emissions. By sector, livestock production contributed 49%–54% toward total agricultural emissions, exceeding emissions of crop production. According to FAO data, the GHG emissions intensity of China’s agricultural sector is lower than that of developed countries and regions. Furthermore, this paper summarizes China’s mitigation potential in feed and livestock production, manure management, fertilizer application, irrigation and tillage practices, as well as challenges faced by China in implementing existing measures and policies for agricultural carbon mitigation and sequestration. Finally, recommendations for future policies and measures are proposed from technological, institutional, and managerial perspectives.